Las medidas cautelares en los centros de rehabilitación social y su impacto socio jurídico en los adultos mayores caso Machala año 2013. - Garrochamba Pereira, Marco (2014)
Departure from our research topic entitled: Precautionary measures in the social rehabilitation centers and partner legal impact on seniors case Machala 2013, we have developed this research with the aim of emphasis on the rights of the elderly adults fees prescribed in our constitution of the Republic in his ast. 35 which states on priority groups and vulnerable groups including girls, children, elderly and terminally ill, that in accordance with Art. 38.7 of the same Code indicating on how to serve their sentences as older adults, either for the crime of imprisonment or detention.